2017
DOI: 10.4172/jpb.1000421
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Therapeutic Potential of Beauvericin: A Short Review

Abstract: An entomopathogenic fungus, Beauveria spp. has been known to have numerous pharmacological and therapeutic implications, especially, in terms of human health making it a suitable for ethnopharmacological use. Beauvericin is a cyclic hexadepsipeptide mycotoxin, a novel bio-metabolite derived from this fungus, exhibiting a very potent anticancer, cytotoxic activities, antiplatelet aggregation and antimicrobial activities. The current review discusses the therapeutic potential of beauvericin including pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…After analyzing the production conditions and the types of pigments produced by B. bassiana, the chemical characteristics of the metabolites are shown in Table 2. (Wat et al, 1977) Beauvericin (3S,6R,9S,12R,15S,18R)-3,9,15-tribenzyl-4,10,16trimethyl-6,12,18tri(propan-2-yl)-1,7,13trioxa-4,10,16triazacyclooctadecane-2,5,8,11,14,17-hexone C45H57N3O9 783.9 g/mol (Sood et al, 2017)…”
Section: Tenellin and Bassianin: Pigments Derived From 2-pyridonementioning
confidence: 99%
See 2 more Smart Citations
“…After analyzing the production conditions and the types of pigments produced by B. bassiana, the chemical characteristics of the metabolites are shown in Table 2. (Wat et al, 1977) Beauvericin (3S,6R,9S,12R,15S,18R)-3,9,15-tribenzyl-4,10,16trimethyl-6,12,18tri(propan-2-yl)-1,7,13trioxa-4,10,16triazacyclooctadecane-2,5,8,11,14,17-hexone C45H57N3O9 783.9 g/mol (Sood et al, 2017)…”
Section: Tenellin and Bassianin: Pigments Derived From 2-pyridonementioning
confidence: 99%
“…For the synthesis of beauvericin via fermentation process it is necessary the presence of glucose as main carbon source for fungal growth. Nevertheless, peptone and NaNO3 are required as nitrogen sources (Sood et al, 2017). The biosynthesis of beauvericin is carried out by the action of beauvericin synthetase, an enzyme with molecular mass of 250 kDa (Peters et al, 1983).…”
Section: Molecular Bases and Metabolic Pathways For The Biosynthesis mentioning
confidence: 99%
See 1 more Smart Citation
“…Beavericin closely resembles the eniatin antibiotics, however, they seem to differ in target (Wang and Xu, 2012). Unlike penicillins and nephrotoxic glycopeptides (eniatin antibiotics) which are cell membrane or cell wall inhibitors, beauvericin targets cell organelles, nucleus and enzymes (Sood et al, 2017). This compound is a specific cholesterol acyltransferase inhibitor.…”
Section: Modes Of Action (Moa) Of Mycotoxins On Biological and Human mentioning
confidence: 99%
“…Tests with bacteria showed that nephrotoxic glycopeptides inhibit the synthesis of cell walls and peptidoglycan synthesis by infringing the addition of new amino acid units to it. The mechanism of this action is reported to involve binding to acyl-D-alanyl-D-alanine terminals of growing peptide chain, inactivating the enzyme transpeptidase and thus prevents further elongation and cross linking of peptiglycan matrix in bacteria (www.medweb (Logrieco et al, 1998;Sood et al, 2017). Beavericin closely resembles the eniatin antibiotics, however, they seem to differ in target (Wang and Xu, 2012).…”
Section: Modes Of Action (Moa) Of Mycotoxins On Biological and Human mentioning
confidence: 99%